Multi-Criteria Decision Making in Travel and Tourism Digitalization: Web-Based Perspective (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The knowledge regarding the use of digitization within tourism industry structures among EU countries, as well as its effects and benefits, is still scarce. This study aims to fill this gap by examining, through a multiple criteria analysis, the level of digital platform application focusing on e-booking use as well the role of COVID-19 on the effects of the digitization processes and its perspectives among tourism structures within EU countries. Thus, this study aims to point out the importance of the application of multi-criteria analysis for business decision-making in tourism through the prism of the adoption of digital platforms, that is, online reservation systems, as the dominant model of modern business for tourist companies. By applying multiple criteria and statistical analysis, this study found a high level of adoption of online booking applications within tourism structures among EU countries, thereby highlighting France as the leading economy in the mentioned context.